KAJIAN TENTANG KARAKTERISTIK MODAL USAHATANI JERUK KEPROK SOE DI KECAMATAN MOLLO UTARA KABUPATEN TIMOR TENGAH SELATAN - Ferdi A. I Fallo; Krisna Setiawan (Politeknik Pertanian Negeri Kupang, 2008)
This research was attributed to know farming capital characteristic tangerine Soe, credit picture in Soe tangerine farming, ijon system description and its impact to tangerine farmer income Soe, supporting internal factor picture tangerine farming success, supporting external factor picture tangerine farming success, families propertied farming distribution and investment feasibility zoom Soe tangerine farming. Result observation to point out that capital that is utilized in Soe tangerine farming ranging from Rp 1.000.000 – Rp 15.000.000. Capital source in capital indigenous farming personal farmer. Soe tangerine farmer never get farming credit of institute whichever but BPLM'S farming help that acquired of on duty agricultural for the price 32.000.000 about farming group. That relief fund is destined for tangerine production behalf Soe. Analysis result points out just vicinity 10% farmer that stills to utilize ijon system divides farming behalf. Meanwhile its rest around 90% does merchant transactions upon harvests raya. Farmer ability in bring off Soe tangerine farming regarded by age, education and experience gets farming. Local transportation medium that is utilized in distribute input and output is Soe tangerine farming was reasonable. Transportation that is utilized in distributes Soe tangerine largely dominated by Villages transportation. Farming contribution to farmer income reaches 70%. In height, that contribution percentage is reverential because a large part farmer just hangs expectation on Soe tangerine farming. Soe Tangerine farming reasonable financial ala to be sighted of NPV'S criterion and B/C Ratio. NPV'S point to tall production capacity is Rp 6.328.624, production capacity is Rp 4.943.328 and production capacity contemns Rp 3.276.715. Meanwhile point B/C Ratio to tall production capacity as big as 18,378, intermediate as big as 23,400 and low as big as 21,285. Keywords: capital characteristic, Soe tangerine farming.